Cover Image, Volume 31, Issue 7. (21st June 2018) - Kamiya, Kouhei; Okada, Naohiro; Sawada, Kingo; Watanabe, Yusuke; Irie, Ryusuke; Hanaoka, Shouhei; Suzuki, Yuichi; Koike, Shinsuke; Mori, Harushi; Kunimatsu, Akira; Hori, Masaaki; Aoki, Shigeki; et al.
Abstract : The cover image, by Kouhei Kamiya et al., is based on the Research Article Diffusional kurtosis imaging and white matter microstructure modeling in a clinical study of major depressive disorder, https://doi.org/10.1002/nbm.3938 .